Studying the Ito ̃ ’s formula for some stochastic differential equation: (Quotient stochastic differential equation) - Abdulghafoor J. Salim; Ali F. Ali (Tikrit Journal of Pure Science)
The aim of this paper is to study It  ’s formula for some stochastic differential equation such as quotient stochastic differential equation, by using the function F (t, x (t)) which satisfies the product   Ito’s formula, then we find some calculus relation for the quotient stochastic differential equation and we generalize the method for all m supported by some examples to explain the method.